Effects of Sleep Disturbances on Behavioral Problems in Preschool Children With Autism Spectrum Disorder - Wang, Ying; Lin, Jingjing; Zeng, Ying; Liu, Yanan; Li, Yamin; Xia, Kun; Zhao, Jingping; Shen, Yidong; Ou, Jianjun (Frontiers in Psychiatry, 2021)
Study objectives: This study aims to identify the characteristic sleep disturbances that affect behavioral problems in children with autism spectrum disorder (ASD), providing a potential direction for sleep and behavioral intervention in ASD. Methods: The data of 513 children with ASD and 246 typically developing (TD) children aged between 2-5 years old were collected. The behavior performance of preschool children was assessed using the Child Behavior Checklist (CBCL) for 1.5-5.0 years old. The Children's Sleep Habits Questionnaire (CSHQ) was used to measure the sleep status of children, and the Social Responsiveness Scale (SRS) was used to measure the severity of disorder. Linear regression analysis was performed to examine the effects of sleep disturbances on behavioral problems, and independent sample t-test was performed to compare the mean of the samples. Results: Compared to TD children, children with ASD had longer sleep onset delay and more night awakenings. The parasomnias score (a subscale of the CSHQ) was significantly associated with the internalizing (β=0.113, P=0.010), externalizing (β=0.128, P=0.006), and total problems (β=0.143, P=0.001) of children with ASD, while this association was not significant in TD children. “Bed wetting” and “Restless and moves a lot” (two items in the CSHQ under parasomnia) significantly only affected the overall behavioral score in children with ASD (P<0.05). Conclusion: Parasomnias, especially bed wetting and restlessness, are specifically associated with the behavioral problems of children with ASD, rather than TD children.